The interactive effects of non-alcoholic fatty liver disease and hemoglobin concentration in the first trimester on the development of gestational diabetes mellitus. - Mengnan Li (Public Library of Science (PLoS), 2021)
Gestational diabetes mellitus (GDM) is associated with adverse perinatal and maternal outcomes. Epidemiological studies have reported that non-alcoholic fatty liver disease (NAFLD) and a high hemoglobin (Hb) concentration are risk factors for GDM in the middle trimester. However, no consistent conclusions have been reached, especially in Chinese pregnant women. A case-control study was conducted to better understand the associations between NAFLD and Hb concentration in the first trimester and the risk of GDM and their interactive effects. Multivariable logistic regression analysis and a cross-product term of Hb and steatosis were used to evaluate the associations between first trimester Hb concentration, steatosis, and GDM and their interactive effects. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using two-sided statistical tests at an alpha level of 0.05. For the study, 1,017 normal pregnant women, and 343 pregnant women diagnosed with GDM (25.22%) were recruited from the First Hospital of Shanxi Medical University, Shanxi Province, China. NAFLD-associated steatosis was found to be independent risk factors for developing GDM compared with grade 0 steatosis, with ORs of 1.98 (95% CI: 1.35-2.89) and 2.27 (95% CI:1.29-3.96), respectively. Meanwhile, a high Hb concentration was found to be a risk factor for developing GDM compared with the normal Hb concentration (OR = 1.88; 95% CI:1.24-2.83). The risk of developing GDM was more pronounced among pregnant women who had both high-grade steatosis and higher Hb concentrations during their first trimester (OR = 6.24; 95% CI: 1.81-23.66). However, we found no significant interactions between Hb concentration and steatosis grade. In conclusion, our study confirmed that a high Hb concentration and NAFLD-associated steatosis during the first trimester play important roles in predicting the risk of GDM in Chinese women. Future studies are required to verify the interactive effects between NAFLD-associated steatosis and Hb concentration.